Comparative Analysis of Educational Systems in Georgia and Abroad (Economics and region, 2018)
This article reviews student’s assessments criteria, educational system’s characteristics, grading norms and methods, knowledge evaluation standards, and analyzes their similarities and differences between Republic of Georgia, Western culture, People’s Republic of China, post-soviet Republics and the United States of America’s educational systems. Besides Georgia’s national strategic goal of joining European Union, it is especially important for us to participate in Europe’s educational processes, the aim of which is to create holistic European educational space. Despite this goal, after reviewing European and Asian (on the example of the Republic of China) higher education criteria and methods for evaluating knowledge levels, we can observe that there are similarities and differences. Despite these differences, Chinese educational system has a lot of similarities with European education system. At the first glance, there are no significant differences between Eastern and Western educational systems. Children go through primarily similar stages of education, regardless of growing up in the East or West.
Keywords: Bologna Process; system of education; еvaluation forms and methods